2007
DOI: 10.1172/jci30380
|View full text |Cite
|
Sign up to set email alerts
|

Thyrocyte-specific Gq/G11 deficiency impairs thyroid function and prevents goiter development

Abstract: The function of the adult thyroid is regulated by thyroid-stimulating hormone (TSH), which acts through a G protein-coupled receptor. Overactivation of the TSH receptor results in hyperthyroidism and goiter. The G s -mediated stimulation of adenylyl cyclase-dependent cAMP formation has been regarded as the principal intracellular signaling mechanism mediating the action of TSH. Here we show that the G q /G 11 -mediated signaling pathway plays an unexpected and essential role in the regulation of thyroid functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
98
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 58 publications
(50 reference statements)
3
98
0
Order By: Relevance
“…The potential significance of TSH action in the initial events associated with Braf-induced thyroid cell transformation is further supported by the attenuated phenotype seen in mice with thyroid-specific deletion of Gsα. However, the fact that Gsα deletion did not prevent development of PTCs is consistent with the evidence that other TSH-activated downstream pathways, such as Gq/G11, also play a critical role in thyroid cell growth (44).…”
Section: Discussionsupporting
confidence: 83%
“…The potential significance of TSH action in the initial events associated with Braf-induced thyroid cell transformation is further supported by the attenuated phenotype seen in mice with thyroid-specific deletion of Gsα. However, the fact that Gsα deletion did not prevent development of PTCs is consistent with the evidence that other TSH-activated downstream pathways, such as Gq/G11, also play a critical role in thyroid cell growth (44).…”
Section: Discussionsupporting
confidence: 83%
“…In an in vitro study, the C636W mutant stimulated the Gs-adenylyl cyclase pathway in a constitutive manner; however, activation of Gq-phospholipase C stimulated by TSH was markedly reduced compared with the WT. Based on these findings, the authors suggested that the lack of goiter in their patient might be due to impairment of the Gq-phospholipase C signal pathway because Gq-phospholipase C is involved in thyroid hormone synthesis and growth of the thyroid gland as well as the Gs-adenylyl cyclase pathway (3). In this context, we compared the activation capacity of Gq-phospholipase C between M453R and M453T; however, both mutants had completely lost the capacity to activate this pathway.…”
Section: Discussionmentioning
confidence: 98%
“…This receptor consists of seven transmembrane domains (TMDs) and a large extracellular domain (ECD) that mediates the effect of TSH in thyroid development, growth, and hormone synthesis (1,2). TSH binds the TSHR and activates two signal transduction pathways: the Gs/adenylyl cyclase and Gq-phospholipase C pathways (2,3). The Gs/adenylyl cyclase system is thought to be important for most TSH-induced effects on the growth and the function of the thyroid gland (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A known TSH-dependent but cAMP-independent signaling pathway arises from coupling of the TSHR to G q/11 proteins, activation of phospholipase C, and formation of inositol phosphates (5,18,19). Phospholipase Cdependent pathways have recently been shown to be required for iodine organification and thyroid hormone secretion and for the adaptive growth of the thyroid gland (20). Finally, G 12/13 coupling of the TSHR has been shown in primary human thyrocytes and was suggested to be related to growth or differen-* This work was supported by the Deutsche Forschungsgemeinschaft Grant TR17, project C4.…”
mentioning
confidence: 99%